Media optimization for the production of cephalosporin C acylase from a novel bacterial source: alcaligenes xylosoxidans MTCC*491 - Nupura, Hirve; Asmita, Tingare; Sharat, B.; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
The Gram-negative bacterium Alcaligenes xylosoxidans MTCC *491 has been studied for the production of cephalosporin C acylase (CCA), a pharmaceutically important enzyme. The enzyme hydrolyses cephalosporin C (CPC), a natural product, to 7-aminocephalosporanic acid, a key intermediate in the production of semisynthetic cephalosporin antibiotics. Effect of medium, pH, temperature, carbon source, nitrogen source and incubation time, on the production of CCA was studied. 7.7 IU/ml activity was obtained when Luria Bertani broth (LB) was used as a fermentation medium. Glucose and galactose increased the enzyme activity by 9 % and 22 %, while all the nitrogen sources tested showed a repressive effect. Maximum CCA activity was observed around the 5(th) day of incubation indicating potential role of CCA in secondary metabolism. pH 8.0 and 40 degrees C were found to be the optimum conditions for acylase activity.
Keywords: alcaligenes xylosoxidans MTCC*491; cephalosporin C (CPC); cephalosporin C acylase (CCA); fermentation carbon source; nitrogen source